Development and Evaluation of an Instructional Module to Promote Career Maturity for Youth with Learning Difficulties - Hutchinson, Nancy L.; Freeman, John G.; Downey, Katherine H.; Kilbreath, Lisa (Canadian Journal of Counselling and Psychotherapy, 1992)
This paper examines the effects of a counselling program designed to promote career maturity among youth with leaming disabilities and other youth at risk of dropping out of school. The steps of the intervention are given in detail and the results of two pilot studies are presented. The first study involved a group of low-achieving students in an integrated career program, while the second study used a group of adolescents with leaming disabilities as subjects. In both cases, the students in the intervention group improved significantly from pre-test to post-test on a measure of career maturity. Students in a control group did not show similar improvement. Most of the improvement in intervention subjects' scores could be attributed to an improved understanding of career options. Implications of the research and plans for future studies are given.